Digital Customer Experience and Purchase Intention in Indonesian SME E-Commerce - Hardiyanto, Feri; Hidayat, Agus Rohmat; Alifah, Nur; Ahmad Rodiansjah, Agis (GEMA EKONOMI, 2026)
Background: The rapid growth of digital commerce in Indonesia has intensified competition among SMEs, requiring firms to enhance digital customer experience (DCE) to influence consumer behavior. While prior studies emphasize technology adoption and trust, limited research examines the integrated mechanism linking DCE, e-commerce adoption (EA), brand trust (BT), and purchase intention (PI) in emerging markets. Objective: This study investigates the influence of DCE on PI through the dual mediating roles of EA and BT among consumers of Indonesian SME products. Method: A quantitative approach using partial least squares structural equation modeling (PLS-SEM) was employed. The model is grounded in the Technology Acceptance Model (TAM), expectation-confirmation theory, and customer experience literature. Data were collected from 380 e-commerce consumers across five Indonesian provinces. Measurement validity and reliability were assessed using convergent validity (AVE) and discriminant validity (HTMT). Result: The measurement model met acceptable criteria (AVE > 0.59; HTMT < 0.85). DCE significantly influences EA (β = 0.438, p < .001) and BT (β = 0.361, p < .001), both of which significantly affect PI. The indirect effect of DCE on PI through EA and BT is β = 0.236 (95% CI [0.158, 0.316]), indicating partial mediation. A significant direct effect remains (β = 0.193, p = .008), yielding a total effect of β = 0.429. Conclusion: DCE plays a crucial role in driving purchase intention directly and indirectly through EA and BT. SMEs should prioritize comprehensive digital experiences to convert interactions into purchase decisions.